The Feature of Picturesque in Vasyl Holoborodko’s Poems (Linguostylistic Studies, 2015)
The article about the analysis of different types of metaphor structures that are used in the poems of Vasyl Holoborodko. The combination of metaphors in author’s poems discover the anexpected connection of associations that are expressed by different parts of speech like nouns, verbs, adjectives. When analyzing the poems we could see that the metaphor features are quite dynamic because of using of verbs. The biggest part of the verb metaphor structures are the personifications.The most often thing in individual style of Vasyl Holoborodko is the noun combination of metaphor context. The most of genitive metaphors are based on comparing of things, features and functions of the objects that surround us.The adjectives as the metaphor epithets very often play key role in the general structure.In this case we are talking about the adjective metaphor that makes the poems more bright and expressive. Key words: the adjective metaphor, metaphor structures, the noun metaphor, the verb metaphor, individual style. References